Participation trends and performance analysis of Turkey's long-distance runs between 2007-2017 - MELDA PELIN YARGIC; NAILA BABAYEVA; MEHMET SINAN İYİSOY; GALIP BILEN KURKLU; GÜRHAN DÖNMEZ (Akademia Wychowania Fizycznego i Sportu w Gdansku, 2019)
Background: Long-distance running events have gained more popularity worldwide over years. However, the number of participants to such events, age and sex distribution of participants may vary by country. Material and methods: We have investigated participation trends and performances of the finishers of three different courses (15km, half-marathon, marathon) in two of the biggest running events in Turkey (The Antalya and Istanbul marathons) between 2007-2017. Results: Our results have shown that runners who completed the 15km course were the highest and marathon finishers were the lowest in number each year. Among native runners, male participation in each distance and event is higher than female participation. Native female marathon finishers increased only by 0.23% in 6 years. In all distances, women run at a lower average speed than men each year. Between 2007-2017, the mean average speed of women were 9.10km/h (±0.18), 9.71km/h (±1.62) and 9.72km/h (±1.73) and the mean average speed of men were 10.45km/h (±2.02), 10.89km/h (±1.83) and 10.40km/h (±1.80) at 15km, 21km and 42km respectively. Conclusion: An important sex gap was observed in participation in long-distance runs in Turkey, which is more pronounced in marathons. Performance analysis showed that females' mean average speed is lower than males' in all distances.